Analysis of the Effect of Red LED and Infrared Flip Flop Frequency on SpO2 Measurement Accuracy - Moch Prastawa Assalim T P; Dyah Titisari; Wahyu Caesarendra; Bagas Angger Prakoso (Indonesian Journal of Electronics, Electromedical Engineering, and Medical Informatics, 2022)
Oxygen saturation is a vital parameter for the early detection of advanced oxygen deficiency. Spo2 is a tool that measures the amount of oxygen in the blood non-invasively. This equipment consists of ophotodiodeiode as a sensor as well as red and infrared LEDs with a flip flop driver circuit that has a certain frequency. In this case, several research projects and equipment on the market have various flip flop frequencies. This research aims to find the best frequency setting value for red and infrared led drivers on SpO2 devices. In this research, a SpO2 that can be adjusted with a flip flop frequency of 400 Hz to 1400 Hz was designed. The SPO2 reading from the sensor is presented on the OLED LCD panel using Arduino Mega as a data processor from the driver frequency output controller. Frequency adjustment for sensor drivers is also at 400 Hz to 1400 Hz. This tool was further used to measure the frequency variation of the flip flop. The measurement results on the subject's finger were then compared with the results of the standard SpO2 tool to see the effect of the frequency value on the level of accuracy of the tool. The results of the comparison data processing showed that the largest error of 0.35% occurred in the SPO2 measurement using the 600 Hz sensor frequency driver, and the smallest error value of 0.07%, occurred in the use of the driver frequency at 1400Hz. These results can be used in the initial design of the production of SpO2 equipment, the higher the frequency, the more accurate it will be. This study only discusses the frequency, whereas the intensity parameters of the red and infrared LEDs also vary. In future research, it would be better to involve the LED light intensity parameter to determine its effect on the accuracy of the tool.